Changes in oral health in patients with behçet's disease: 10-Year follow-up - (:unkn) unknown (My University, 2011)
Giriş: Bu araştırmanın amacı Behçet hastalarında (BH) 10 yıllık dönemde oral sağlıktaki değişimleri incelemektir. Hastalar ve Yöntemler: Bu retrospektif araştırmaya 10 yıl süresince düzenli olarak klinik, laboratuvar ve oral sağlık değerlendirmeleri yapılan 18 BHlı hasta seçildi (K/E: 12/6, yaş ort.:36.4 ± 9.9 yıl). Oral sağlık dental ve periodontal indeksler ile değerlendirildi. Hastalara her muayenede düzenli olarak oral hijyen eğitimi verildi. Oral ülser sayısı/ay kaydedildi ve hastalık şiddet skoru hesaplandı. Bulgular: Diş fırçalama sıklığının 10 yıllık izlem sonrasında (median:1.2) başlangıç dönemine (median:1) göre artış gösterdiği ama anlamlı farklılığa ulaşmadığı görüldü (p=0.06). Başlangıç ve kontrol dönemlerinde dental ve periodontal indeks skorlarında anlamlı farklılık tespit edilmedi (p>0.05). Aylık oral ülser sayısı ise 10 yıllık izlem döneminde (median:1) başlangıç dönemine göre (median:6) anlamlı olarak azaldı (p=0.000). Sonuçlar: Behçet hastalarında ağrılı ülser varlığının oral sağlığı olumsuz yönde etkilemesine rağmen, 10 yıllık izlem döneminde oral hijyen eğitimi ve motivasyon ile dental ve periodontal sağlığın stabil kaldığı belirlendi. Ancak oral hijyenin iyileştirilmesi ile oral ülserin azalması arasındaki ilişkinin daha iyi değerlendirilebilmesi için yeni çalışmalara ihtiyaç vardır.

Objective: The aim of this retrospective study was to evaluate the changes in oral health parameters in patients with Behçet s disease (BD) in a 10-year follow-up study. Patients and Methods: Eighteen BD patients (F/M: 12/6, mean 36.4 ± 9.9 years) followed regularly by clinical, laboratory and oral health examinations for 10 years, were included in the study. Oral health was evaluated by dental and periodontal indices. Patients were given oral hygiene education regularly in each visit. In addition, the number of oral ulcers per month was noted and a disease activity score was calculated. Results: Although the frequency of tooth brushing was higher for the 10-year follow up (median:1.2) than for the baseline (1.0), no significant difference was observed (p=0.06). Also there were no significant differences for the scores of periodontal indices and dental indices at baseline and follow-up (p>0.05). The number of oral ulcers/month was lower at follow-up (median:1) compared to baseline (median:6) (p=0.000). Conclusion: Although painful ulcers affect oral health negatively, dental and periodontal health remained stable in a 10-year follow-up in BD patients with motivation and education for oral hygiene. However, further studies are required to demonstrate whether better oral hygiene effects the course of oral ulcers.
Behçet hastalarında oral sağlığın değişimi: 10 Yıllık izlem çalışması
Keywords: Genel ve Dahili Tıp